2007
DOI: 10.1890/06-1128.1
|View full text |Cite
|
Sign up to set email alerts
|

Human Influence on California Fire Regimes

Abstract: Periodic wildfire maintains the integrity and species composition of many ecosystems, including the mediterranean-climate shrublands of California. However, human activities alter natural fire regimes, which can lead to cascading ecological effects. Increased human ignitions at the wildland-urban interface (WUI) have recently gained attention, but fire activity and risk are typically estimated using only biophysical variables. Our goal was to determine how humans influence fire in California and to examine whe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

28
462
2
6

Year Published

2010
2010
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 570 publications
(516 citation statements)
references
References 40 publications
28
462
2
6
Order By: Relevance
“…However, studies on high population density in large urban areas, such as those by GonzalezOlabarria et al (2011) for north-eastern Spain, Argañaraz et al (2015) for Argentina, and Beccari et al (2015) for northern Italy, found low fire occurrence. This may have been caused by the lower availability of fuel to support HCFs in highly developed urban areas (Syphard et al 2007(Syphard et al , 2009Price and Bradstock 2014). Donoghue and Main (1985) observed an increase of HCF occurrence related only to non-metropolitan population density.…”
Section: Predictors For Long-term Studiesmentioning
confidence: 99%
“…However, studies on high population density in large urban areas, such as those by GonzalezOlabarria et al (2011) for north-eastern Spain, Argañaraz et al (2015) for Argentina, and Beccari et al (2015) for northern Italy, found low fire occurrence. This may have been caused by the lower availability of fuel to support HCFs in highly developed urban areas (Syphard et al 2007(Syphard et al , 2009Price and Bradstock 2014). Donoghue and Main (1985) observed an increase of HCF occurrence related only to non-metropolitan population density.…”
Section: Predictors For Long-term Studiesmentioning
confidence: 99%
“…The presence of humans in the landscape can alter patterns of ignitions (Penman et al 2013a;Collins et al 2015;Mann et al 2016), often resulting in an overall increase in the number of ignitions per year (Syphard et al 2007;Syphard et al 2009;Plucinski et al 2014;Price 2015). Fragmentation and manipulation of forests through expansion of agriculture and human settlements has created discontinuities in fuels thereby influencing fire spread patterns (Finney 2007;Price and Bradstock 2010;Salis et al 2014) and surface fire behaviour (Agee et al 2000).…”
Section: Introductionmentioning
confidence: 99%
“…Human activities have altered the regime of wildfires beyond their natural historic range (Syphard et al, 2007;Batllori et al, 2013), often driven by changes in landuse (Pausas et al, 2008). In Mediterranean Europe, the abandonment of farmland and the plantation of commercial forests (for the wood and paper industry) have contributed to the increased frequency and spatial extent of wildfire (Moreira et al, 2001;Pausas, 2004;Pausas et al, 2004a).…”
Section: Introductionmentioning
confidence: 99%